2018
DOI: 10.1093/ecco-jcc/jjy052
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin D on Intestinal Inflammation and Faecal Microbiota in Patients with Ulcerative Colitis

Abstract: Vitamin D supplementation was associated with reduced intestinal inflammation in patients with active UC, with a concomitant increase in Enterobacteriaceae but no change in overall faecal microbial diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
2
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 58 publications
3
70
2
7
Order By: Relevance
“…(Gammaproteobacteria) was detected in stool. Interesting observation regarding decrease in abundance of Clostridiales, especially Faecalibacterium prausnitzii and Ruminococcaceae was associated with the inflamed biopsy of UC patients what correlates with previous study 62 . Reduction of Faecalibacterium is set to be primarily associated with ileal CD 70 and decrease of Firmicutes with lower level of vitD 58 .…”
supporting
confidence: 85%
“…(Gammaproteobacteria) was detected in stool. Interesting observation regarding decrease in abundance of Clostridiales, especially Faecalibacterium prausnitzii and Ruminococcaceae was associated with the inflamed biopsy of UC patients what correlates with previous study 62 . Reduction of Faecalibacterium is set to be primarily associated with ileal CD 70 and decrease of Firmicutes with lower level of vitD 58 .…”
supporting
confidence: 85%
“…The impact of vitamin D on DSS colitis and the faecal microbiome has been previously reported by us [ 7 ] and others [ 44 , 45 ], and recently also in a small series of IBD patients [ 46 , 47 ]. In the current study, UVR was associated with changes in the faecal microbial composition after DSS exposure that differed from the changes described in non-DSS mice.…”
Section: Discussionsupporting
confidence: 60%
“…Megasphaera and Lactobacillus were enriched at week 4, but still comprised a relatively low abundance overall (122). A study of active and inactive UC patients found overall microbiota diversity to be unchanged following 8 weeks of vitamin D supplementation, but a significant increase in abundance of Enterobacteriaceae (phylum: Proteobacteria) in UC patients (123). Healthy control mice fed a high vitamin D diet (10,000 IU/kg) displayed reduced species diversity and were enriched with Paludibacter (phylum: Bacterioidetes) and Sutterella (phylum: Proteobacteria), the latter of which was also enriched in DSS colitis mice (124).…”
Section: Vitamin D Supplementation and Changes In Autoimmune Disease mentioning
confidence: 99%